Sprinkler irrigation - Sapir, Elimelech (Mashav,Cinadeco, 2004)
The main topics of this booklet deal with the technology and theory of sprinkler irrigation. Related subjects such as soil-water-plant relations, fertigation, irrigation systems design,...